Influence of Extrusion Processing on Tannin Reduction and Oil Loss in Flaxseed (Linum usitatissimum L.) Meal. Issue 1 (24th September 2012) - Imran, Muhammad; Anjum, Faqir M.; Butt, Masood S.; Sheikh, Munir A.
Abstract This study focuses on the effects of extrusion processing on tannin reduction and oil loss in flaxseed (Linum usitatissimum L.) meal. The ranges of processing variables selected using central composite design were: barrel exit temperature (BET) of 76.3–143.6C; screw speed (SS) of 59.6–160.5 rpm and feed rate (FR) of 26.4–93.6 kg/h. The experimental values of tannin reduction and oil loss obtained were from 42.9 to 77.2% and from 1.5 to 7.6%, respectively. Optimal operating conditions were established: BET (137.9C), SS (156.8 rpm) and FR (26.4 kg/h) for maximum (77.2%) reduction of tannins and minimum (3.7%) oil loss. Response variables were mainly dependent on BET, whereas significant reduction of tannins and oil loss was achieved in studied BET and SS combination of process parameters (P ≤ 0.05). The results of this study demonstrated that significant reduction of tannins with minimum oil loss in flaxseed meal can be achieved commercially using an extruder. Practical Applications The extrusion technology has been explored to reduce the toxic compounds in different oilseed meals and oil extraction for production of functional foods. However, the production of extruded oilseed meals with high content of lipids (>16%) is limited as the oil percolation creates problem to preserve extrudates and maintain the hygienic condition of extruder plant. This study suggested that there is an immense possibility to use single‐screw extrusion cooking for reduction of tannin content with minimum oil percolation during production of extruded flaxseed meal for commercial food or feed purposes.